Church Talks on Peace Talks: The United Church of Christ in the Philippines (UCCP) and the Duterte Presidency - Crisostomo-Pilario, Junesse d R. (Social sciences and missions, 2022)
At the beginning of Duterte’s term, the UCCP extended support for his administration. This was based on the alignment between the church and the President’s goals of purging of systemic sins in Philippine society through peacemaking. Using the theological rhetoric of the social gospel as framework, the UCCP first considered President Duterte as the ideal rhetorical audience who can address urgent needs through the resumption of peace talks. However, after two years of Duterte’s broken campaign promises, the church began to address its own constituents as the rhetorical audience they need to persuade in order to purge the systemic sins of Philippine society. Church members must be in solidarity with their leaders in opposing President Duterte’s policies. Through a shift from a rhetoric of transcendence to that of resistance, the church persuades its audiences of the sacredness of political support or opposition, giving religious justification to the mission of social reform.